Consuming Reality - Deery, J. author. aut Link
XI, 225 p.
Keywords: Consuming Reality examines TV's response to the increasing pressure to brand content in a post-advertising era. June Deery's comprehensive analysis of the commercial practices found in popular reality programming reveals links to larger trends such as the sentimental dissemination of capitalist and nationalist ideologies, the professionalization of social relationships (including conceptions of self), and the mainstreaming of PR techniques in everyday life. Examining topics such as reality formats as pseudo-events, product placement, donorship, TV-web branding, making over homes/bodies as properties, consumer identity and pathology, Disney, and the American Dream, this book engages in a comprehensive examination of RTV's advertising and promotional strategies, as well as the commodification of viewers, of TV participants, of ideologies, dreams, and ideas.